Arduino- based temperature monitoring and control via can bus - Mohammad Huzaifah, Che Manaf (2016)
This project presents the Arduino-based Temperature Monitoring and Control via CAN Bus. Controller Area Network (CAN) bus that is designed to allow microcontrollers and other electronic devices to communicate with each other within a vehicle without a host computer. It was originally designed for multiplex electrical wiring within automobile, but also used in many other contexts. The desired temperature is obtained by controlling the ON and OFF states of the heater and fan. The temperature is controlled using Arduino Uno that is interfaced with the plant using CAN Bus that provides the communication between Arduino and LCD display.